Impact of Trekking on Teachers’ Job Performance and Students’ Academic Work in Basic Schools in Federal Capital Territory, Abuja, Nigeria - Ukozor, Conrad Ugochukwu (MultiTech Publisher, 2024)
They assessed the impact of trekking on teachers’ job performance and students’ academic work in basic schools in the Federal Capital Territory, Abuja, Nigeria. The study employed survey research design. The population of this study comprises all the teachers and basic SIS students in all six area councils of FCT. The sample size of the study was made up of two hundred and seventy-eight (278) and three hundred students (300). The sample basic schools were selected using a random sampling technique. The research instrument used for data collection in this study is a researcher-designed questionnaire. Experts in educational management and English departments examined the instrument's face and content validity as well as its language appropriateness. A pilot study was conducted in basic schools not included in the study. In order to find out the reliability coefficient of the research instrument to be used. The frequency, percentages, mean, and standard deviation were used at a descriptive level. The study concluded that the disruption of curriculum implementation in the schools, the deterioration of teachers’ health, mental health, frustration, and low motivation and exhaustion, and texhaustion, developingtion, psychological problems, as well as the reduction in teachers’ job productivity and reduction in research hours of teachers, are the impacts of trekking on teachers’ job performance in basic education in the Federal Capital Territory, Abuja, and late coming to class, reduction in hours of studies, and lower students’ performance, physical exhaustion, and mental health. Affect students’ health, diminish students ability to meet academic expectations, and compete effectively with peers, and frustration and low motivation to learn are the impact of trekking on students’ academic performance in basic education in the Federal Capital Territory, Abuja. Based on the finding, the government, the study recommends that g should provide school buses to all basic schools in the Federal Capital Territory, Abuja, Nigeria, to aid teachers’ and students’ movement to schools. Private institutions and community members can also donate school buses to schools. The government should build more basic schools across the territory to allow students access to schools closer to their homes. This will help to reduce students’ trekking to schools in the territory.